Significance of intrarenal B and T lymphocytic infiltrates in lupus nephritis. Issue 1 (July 2016) - Emara, Nashwa M.; Abou Elmahasen, Mona A.; Omar, Eman S.; El-Saidy, Adel Z.; El Shawarby, Zeinab I.; Youssef, Samia A.
Abstract : Background: Lupus nephritis (LN) is one of the most serious complications of systemic lupus erythematosus. The true prevalence of clinical LN in individuals with systemic lupus erythematosus is probably around 50%, being higher in certain ethnic groups and in children. It was hypothesized that intrarenal B cells form a part of a local system, with pivotal involvement in the pathogenesis of LN. It enhances immunological responses and exaggerates the local immune response to persisting autoimmune damage in the tubulointerstitium. T cells cause tissue injury by activating and providing help to nephritogenic antibody-producing B cells, recruiting macrophages and dendritic cells, and producing cytokines. Aim: This retrospective study aimed to assess intrarenal B and T lymphocytic infiltrates in cases of LN using CD20 and CD3 and determine their possible value in LN and their possible relation to clinical outcome. Results: Intrarenal B and T cells were more likely to be associated with class IV LN. The LN activity index, the chronicity index, proteinuria, and serum creatinine had a significant statistical correlation with intrarenal B-cell and T-cell infiltrates. Conclusion: The current study concludes that interstitial inflammatory infiltrates and chronicity index but not activity index could be used as prognostic factors in LN and also concludes that the presence of intrarenal B : T-cell infiltrates and its grading could be used as a prognostic factor in patients with LN. It shall provide a hope for the management and improvement of prognosis of LN patients, especially the resistant cases, with trials with anti-CD20 drugs.